Optimization and Control of Bilinear Systems Theory, Algorithms, and Applications - Pardalos, Panos M.; Yatsenko, Vitaliy A. (Springer Optimization and Its Applications, 2008)
The purpose of this book is to acquaint the reader with the developments in bilinear systems theory and its applications. Bilinear systems can be used to represent a wide range of physical, chemical, biological, and social systems, as well as manufacturing processes, which cannot be effectively modeled under the assumption of linearity. This book provides a unified approach for the identification and control of nonlinear complex objects that can be transformed into bilinear systems, with a focus on the control of open physical processes functioning in a non-equilibrium mode. The material is intended for graduate students, researchers, and specialists engaged in the fields of quantum and molecular computing, control of physical processes, biophysics, superconducting levitation, physical information science, mathematics, and engineering.